2021
DOI: 10.1038/s41598-021-83902-w
|View full text |Cite
|
Sign up to set email alerts
|

Native and invasive ants affect floral visits of pollinating honey bees in pumpkin flowers (Cucurbita maxima)

Abstract: Global pollinator decline is a major concern. Several factors—climate change, land-use change, the reduction of flowers, pesticide use, and invasive species—have been suggested as the reasons. Despite being a potential reason, the effect of ants on flowers received less attention. The consequences of ants being attracted to nectar sources in plants vary depending upon factors like the nectar source's position, ants' identity, and other mutualists interacting with the plants. We studied the interaction between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Indeed, plant communities in savannah and forest are different, so these different sites offer neither the same quality nor the same quantity of resources. For example, some plants offer not only nesting sites but also food resources (floral and non‐floral nectars) (Pierce, 2019; Unni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, plant communities in savannah and forest are different, so these different sites offer neither the same quality nor the same quantity of resources. For example, some plants offer not only nesting sites but also food resources (floral and non‐floral nectars) (Pierce, 2019; Unni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, plant communities in savannah and forest are different, so these different sites offer neither the same quality nor the same quantity of resources. For example, some plants offer not only nesting sites but also food resources (floral and non-floral nectars) (Pierce, 2019;Unni et al, Another reason could be the availability of tree species with or without extra-floral nectar (Moura & Del-Claro, 2023). Thus, plant species richness and plant density can influence ant species richness (Ribas et al, 2003;Vasconcelos et al, 2019).…”
Section: Ant Diversity In the Three Different Habitatsmentioning
confidence: 99%
“…Floral and extrafloral nectar are also widespread carbohydrate-rich resources linked to invasive ant success [39][40][41][42]. Invasive ants visiting plantassociated carbohydrate-rich resources often affect other insect-plant interactions with consequences for pollinators [43,44], plant reproduction [45,46], and herbivory [47]. The availability of honeydew to invasive ants depends on the honeydew producers, their host plants and natural enemies, and resident ants, all of which may respond to climate change independently.…”
Section: Acquiring Plant-based Carbohydrate Resourcesmentioning
confidence: 99%
“…However, mutualistic ants attracted by plant-based resources may forage on entire plant structures, including inflorescences and flowers. Although extrafloral nectar is a sugar-rich reward, ants also forage on plant reproductive parts looking for floral resources (such as nectar and pollen) and potential prey (such as floral herbivores) (Blüthgen et al, 2003;Blüthgen & Fiedler, 2004;Davidson et al, 2003;Sinu et al, 2017;Unni et al, 2021;Hanna et al, 2015;Fuster et al, 2020). The additional foraging behavior on these reproductive plant parts may negatively affect mutualistic plant-pollinator interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using dummy ants on flowers, Assunção et al (2014) showed that pollinators easily recognize ant shape and color, which significantly reduced floral visitation rate and fruit production. When ants are present, floral visitors may approach a flower, but can also change their behavior by reducing the time spent on flowers (Aguirre-Jaimes et al, 2018;Assunção et al, 2014;Ness, 2006;Sousa-Lopes et al, 2020;Villamil et al, 2018;Sinu et al, 2017;Unni et al, 2021;Hanna et al, 2015;Fuster et al, 2020), or they will not come into contact with the reproductive parts, becoming ineffective in pollination. In the Brazilian tropical savannah, smaller bees tend to spend more time analyzing flowers with tending ants before approaching, since they are more affected by ant presence on flowers than larger bees (Assunção et al, 2014;Barônio and Del-Claro, 2017).…”
Section: Introductionmentioning
confidence: 99%